CATALYTIC POTENTIAL OF GOURD PEEL PEROXIDASE FOR BIODEGRADATION OF SYNTHETIC RECALCITRANT DYES FUCHSIN ACID AND CRYSTAL VIOLET - A. Tabassum; H. N. Bhatti; S. Nouren; M. Zahid (Journal of Animal and Plant Sciences, 2015)
Peroxidases can be used in decolorization processes and the treatment of textile effluents. In this context, the current study evaluates the potential of the partially purified gourd peel peroxidase in decolorization of triarylmethane class dyes; fuchsin acid and crystal violet. For this purpose, some important process parameters like pH, temperature, time of incubation, dye concentration, enzyme and H2O2 dose were optimized. Besides this, the effect of mediators was also evaluated on the performance of peroxidase. 98.25 % decolorization of fuchsin acid (50 mg/l) was achieved at 36 Uml−1 enzyme dose and 1.6 mM H2O2 concentration, in the presence of 0.2 mM vanillin, whereas pH, temperature and time for maximum decolorization were recorded to be 2.0, 30 0C and 30 min respectively. However, at the same H2O2 and vanillin concentrations, 85.21 % decolorization of crystal violet was achieved at a dye concentration of 40 mg/l and enzyme dose of 28 U/ml. The pH, temperature and time for maximum decolorization were reported to be 4.5, 50 0C, respectively. Thus, the data indicates that gourd peelperoxidase could be a potential source for developing an inexpensive and efficient method for the treatment of recalcitrant fuchsin acid and crystal violet dyes that are potentially toxic.
Keywords: Gourd peel peroxidase; Decolorization; Triarylmethane dyes; Crystal violet; Fuchsin acid; Vanillin